Sales Boosting Strategy Through Live Streaming: Communication Skills And E-Commerce Advertising’s Vehemence - Novilia, Fitri; Suryana, Suryana; Hendrayati, Heny; Saputra, Yori Andes; Furqon, Chairul (UPT Publikasi Ilmiah UNISBA, 2025)
This study aims to analyze sales-boosting strategies for fashion products through live streaming by MSMEs in Indonesia, focusing on the roles of communication skills, platform advertising, and pricing strategies. A mixed-method approach is employed, combining qualitative data gathered through in-depth interviews with five experienced MSMEs in the fashion sector in West Java and quantitative data collected from 101 active MSMEs using purposive sampling from industry databases. The data were analyzed using Structural Equation Modeling (SEM) and PLS to examine the relationships among variables. The results indicate that practical communication skills during live streaming and the optimal use of platform advertising significantly increase sales volume. Competitive pricing strategies also play a crucial role in supporting successful live-streaming sales. The practical implications highlight the importance of MSMEs enhancing their communication proficiency and digital marketing strategies to leverage live-streaming opportunities, increasing their competitiveness, and contributing to national economic growth.